The Impact of Business Intelligence (BI) Competence on Customer Relationship Management (CRM) Process: An Empirical Investigation of the Banking Industry - Ali Mortezaei; Mohamad Sadegh Sangari; Salman Nazari-Shirkouhi; Jafar Razmi (Journal of Information Technology Management)
Nowadays, establishing long-term and effective relationships with customers is a key factor in understanding customers’ needs and preferences and achieving competitive advantage. In addition, companies are facing with a growing need for information and analytical knowledge about their customers, market, competitors, organizational environment, and other factors affecting their business. Business intelligence has been considered as a response to this need. The purpose of this study is to investigate the role of business intelligence competence in improving customer relationship management process. Based on the literature review and the competence – capability relationship paradigm, a conceptual model was developed comprising of different dimensions of business intelligence competence and customer relationship management processes. The data were collected from the banking sector and partial least squares structural equation modelling was employed for data analysis. Empirical results showed that organizational business intelligence competence, comprising of managerial, technical, and cultural competence, has a significantly positive impact on enhancing capabilities of customer relationship management process including initiation, maintenance, and termination of the relationship.